EXTENSION WORKERS UTILIZATION OF E-EXTENSION IN DISSEMINATION OF AGRICULTURAL TECHNOLOGY IN GOMBE STATE, NIGERIA - Inuwa, M.P.; Murtala, N.; Garba, M. (Nigerian Journal of Agriculture and Agricultural Technology, 2024)
The study assessed extension workers’ utilization of E-extension in the dissemination of agricultural technologies in Gombe State, Nigeria. A total of 142 respondents were selected and data were collected using structured questionnaire. The data were analyzed using descriptive statistics. The result revealed that the mean age of the respondents was 42.5 years. Majority (73.2%) of the respondents were males and most (98.6%) of them were married. The result indicated that respondents had mean household size of 5 persons and (88.9%) of them had tertiary education. Furthermore, the mean working experience of the respondents was 10.0 Years. The major e-resource tools used in the dissemination of agricultural technologies were mobile phone ( = 2.86), whatsApp ( = 2.35) and radio ( = 2.01). The constraints faced by respondents in e-extension utilization were poor and unstable power supply (1st), poor attitude of extension workers toward e-resource tools usage (2nd) and inadequate facilities (3rd). The study concluded that extension workers were relatively using e-resource tools such as radio, mobile phone and television in the dissemination of agricultural technology. The study recommended that government and other development agencies should provide and improve rural electricity and telecommunication network.